The effect of preoperative stoma site marking on risk of stoma‐related complications in patients with intestinal ostomy — A systematic review and meta‐analysis. (6th April 2022) - Ambe, Peter C.; Kugler, Charlotte Mareike; Breuing, Jessica; Grohmann, Erich; Friedel, Julia; Hess, Simone; Pieper, Dawid
Abstract: Aim: This systematic review and meta‐analysis aimed to investigate the effect of preoperative stoma site marking on stoma‐related complications in patients with intestinal ostomy. Methods: MEDLINE, Embase, CENTRAL, CINHAL, and Google Scholar were searched up to August 2021 for randomised controlled trials (RCTs) and nonrandomised studies of interventions (NRSI) that involved patients with intestinal ostomies comparing preoperative stoma site marking to no marking and which reported at least one patient‐relevant outcome. Outcomes were prioritised by stakeholder involvement. Random‐effects meta‐analyses produced odds ratios (ORs) or standardised mean differences (SMD) and 95% confidence intervals (CIs). The ROBINS‐I tool and the GRADE approach were used to assess the risk of bias and certainty of evidence, respectively. Results: This review included two RCTs and 25 NRSI. The risk of bias was high in RCTs and serious to critical in NRSI. Although preoperative site marking reduced stoma‐related complications (OR: 0.45, 95% CI: [0.31–0.65]), dependence on professional or unprofessional care (narrative synthesis), and increased health‐related quality of life (SMD: 1.13 [0.38–1.88]), the evidence is very uncertain. Preoperative site marking may probably reduce leakage (OR: 0.14 [0.06–0.37]) and may decrease dermatological complications (OR: 0.38 [0.29–0.50]) and surgical revision (OR: 0.09 [0.02–0.49]). The confidence in the cumulative evidence was moderate to very low. Conclusion: Despite low quality evidence, preoperative stoma site marking can prevent stoma‐related complications and should be performed in patients undergoing gastrointestinal surgery given that this intervention poses no harm to patients.